From the files of a security expert witness - Sennewald, Charles A. 1931- (Butterworth-Heinemann, 2013)
This book guides the reader through the experience of testifying in court on security issues in civil litigation.Encompassing aspects of criminal and tort law, all within the context of forensic security consulting, this book offers valuable insights from an experienced security professional